B18 Transcriptome profiling of B6.HttQ111/+ hepatocytes in response to chemical perturbagens. (13th September 2016) - Bragg, Bobby; Coffey, Sydney; Ament, Seth; Price, Nathan; Carroll, Jeffrey
Abstract : Background: We are interested in detecting the earliest molecular consequences of endogenous mutant Huntingtin expression. These early consequences can be difficult to detect when cells are in a steady state, so we are using chemical perturbations to investigate how mutant Huntingtin alters dynamic cellular responses. Our own data indicate that environmental perturbations, such as a high-fat diet, can induce widespread transcriptome modification in wild-type cells that is absent or unique in cells expressing mutant Huntingtin, making this approach useful to understanding the effects of mutant Huntingtin and identify potential therapeutic targets. Aims: We aim to detect the early molecular consequences of endogenous mutant Huntingtin expression in B6.HttQ111/+ hepatocytes. Methods: We are using two distinct perturbations to stress primary hepatocytes; the topoisomerase II inhibitor, Etoposide, to induce DNA damage, and the Carnitine Palmitoyl Transferase-1 inhibitor, Etomoxir, to inhibit fatty acid β-oxidation. Results/outcome: We have generated transcriptomic profiles using RNAseq of samples collected across a dense time course of perturbagen exposure. These profiles reveal widespread transcriptional changes, which are consistent with the mechanisms of action of these agents. We are using these transcriptomic data to build in silico models of hepatocyte metabolism and response to DNA damage. We are currently validating our in silico models by measuring expression and activation of specific proteins predicted to be altered in these perturbed states. We will present cross-sectional data describing the impact of CAG expansion in Htt on transcriptional responses to chemical perturbation in primary hepatocytes. Conclusions: We conclude that the transcriptome is altered in response to environmental perturbagens in B6.HttQ111/+ hepatocytes. Support: CHDI foundation, Huntington Society of Canada